Dairy Farmer Resource Competency Development Model In Supporting The Development Of Tourism Village Area - Muhammad Aufa Nabil; Lucia Cyrilla; Iyep Komala (UNIVERSITAS PAKUAN, 2025)
The purpose of this study was to evaluate good dairy farming practices and good milking practices in dairy farms in Tajur Halang Village, to determine the perceptions of farmers, village administrators, and local governments towards the development of dairy farmer competencies for the development of tourist villages, and to formulate a livestock resource development model. This study was designed as a descriptive research. The instrument used in this study are a 4-point Likert scale questionnaire, and Good Dairy Farming Practices (GDFP), and Good Milking Practices (GMiP) evaluation form. Data collection was conducted through interviews with 45 dairy farmers, village administrators, and local governments, Focus Group Discussions (FGDs) on the solidarity of alumni of the Indonesian People's Animal Husbandry School (SASPRI), while the formulation of a model for improving dairy farmer competencies was carried out using the Participatory Rural Appraisal technique (PRA). The results showed that the GDFP and GMiP values ​​of dairy farms in Tajur Halang Village were in the